2013
DOI: 10.2478/amma-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Principles of the Upper Front Teeth: Application of Golden Proportion (Levin) and Golden Percentage (Snow)

Abstract: Objective: The objective of our work is to examine the presence of the much-discussed golden proportion provided by Levin, and of the golden percentage (Snow), on the widths of maxillary anterior teeth, by measurements made on digital images. Material and method: The material of this study consists of digital photographs taken of subjects with natural and esthetic teeth. We took photos of 68 subjects (35 women and 33 men), between 19 and 26 years. Using a computer program, we made the necesarry measurements, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…However, no significant difference between both groups was found. This result is similar to the results of some previous studies conducted in India [14,19,[24][25][26][27][28], Iran [29][30][31], Pakistan [32][33][34], Malaysia [35], Jordan [36], Brazil [37], Romania [38], Nepal [39], China [40], Korea [41], Hungary [42], and in Irish, Iraqi, and Kurdish samples for the canine to lateral ratio [43,44]. However, our results contrast other studies conducted among other Indian [45] and Pakistani [46] samples, which found the golden ratio suitable for esthetic appearance.…”
Section: Discussionsupporting
confidence: 91%
“…However, no significant difference between both groups was found. This result is similar to the results of some previous studies conducted in India [14,19,[24][25][26][27][28], Iran [29][30][31], Pakistan [32][33][34], Malaysia [35], Jordan [36], Brazil [37], Romania [38], Nepal [39], China [40], Korea [41], Hungary [42], and in Irish, Iraqi, and Kurdish samples for the canine to lateral ratio [43,44]. However, our results contrast other studies conducted among other Indian [45] and Pakistani [46] samples, which found the golden ratio suitable for esthetic appearance.…”
Section: Discussionsupporting
confidence: 91%
“…These studies and their outcomes are summarized in Table 3. Over half (54%) of the reviewed articles 49–55 advocated that none of the proportions were suitable, whereas the remaining articles proposed that the golden percentage may be applicable if clinicians took into account the ethnic background of the patient 56–61 …”
Section: Resultsmentioning
confidence: 99%
“…Over half (54%) of the reviewed articles [49][50][51][52][53][54][55] advocated that none of the proportions were suitable, whereas the remaining articles proposed that the golden percentage may be applicable if clinicians took into account the ethnic background of the patient. [56][57][58][59][60][61] Aristeguieta's study 55 was more comprehensive and attempted to find the ideal proportions by making standardized photographs of 351 subjects and digitally measuring the proportions of their maxillary anterior teeth. They found that no universal model can describe the whole population but were able to identify consistent proportions within small subgroups.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Subsequently, Ward proposed use of RED proportions, another method for determining the ideal size and position of the anterior teeth that is based on a ratio of progress of 70% between teeth and a width/length ratio of 78%. Numerous studies have refuted the golden proportions proposed by Levin and the percentages suggested by Snow, [25][26][27][28][29] although a single study found these values, albeit to a negligible degree 30 ; these findings revealed that dento-dental esthetics cannot be restricted to a mathematical model.…”
Section: Discussionmentioning
confidence: 99%